Effect of lossy thin-walled cylindrical food containers on microwave heating performance. (January 2023) - Zhu, Huacheng; Su, Junhao; Yang, Fengming; Wu, Yuping; Ye, Jinghua; Huang, Kama; Yang, Yang
Abstract: Cylindrical containers are commonly used in microwave food processing applications. However, due to the shape effect, microwave energy mainly focuses in the center of the sample within the container, leading to a nonuniform temperature gradient between the inner and outer layers of the sample. Employing a lossy container may be an effective method to address this issue because the heat conduction from the container's wall or the microwave's interaction with the container edge can compensate for the lack of heating in the outer layer. Multiphysics modeling is a powerful tool for uncovering the effect of the lossy container on microwave heating performance. However, noncompliance between the fine and coarse mesh elements at the thin-walled boundary of the container will generate a huge number of irregular meshes, which will not only lead to excessive computational costs but also lead to the possibility of calculation error of the boundary flux. To overcome this difficulty, a fast simulation method based on transformation optics is proposed to analyze the effect of lossy containers on microwave food processing performance in this paper. By using the proposed method, the calculation efficiency can be increased by up to 800% with comparable or even better accuracy than the traditional method. Meanwhile, the results show that the lossy container can improve the temperature uniformity around microwaved food but it will slightly reduce the heating efficiency due to energy loss within the container. This paper offers an efficient and fast way to analyze microwave food heating processes with a thin-wall structure. Furthermore, the discussion on the feasibility of using lossy containers to improve the microwave heating uniformity will also contribute to the further application of microwave cylindrical food processing. Highlights: Microwave heating models with lossy thin-walled cylindrical containers were realized by transformation optics. Compared with traditional method, this method can improve the computing efficiency by 8 times with a wall thickness of 1 mm. The influence of container's material, size and wall thickness on microwave heating is analyzed. Employing lossy container can weak the phenomenon of thermal focus during microwave heating cylinder food.